TEXT TYPES USED IN THE TEXTBOOKS: A SYSTEMIC LINGUISTIC–BASED STUDY - Inatigris Anggriani Harahap; Amrin . Saragih; Zainuddin . Zainuddin (Universitas Negeri Medan, 2022)
In teaching, almost all schools use textbooks. In teaching, the schools give the textbooks to students as the medium of teaching. The textbooks do not only include lessons and practices, but they also include texts and even various text types. The text types are given to the students as medium of practicing the lessons that the students focusing. Halliday (1989:12) states context consists of three aspects, namely field, tenor and mode. The objective of this study is to reason for the various text types are realized in the textbooks of the first Grade of State Islamic School. Donal ( 2010: 29) states that qualitative research is a study that aims to understand a phenomenon that focuses on the total picture. Research design in this study was done by descriptive qualitative research. Data analysis in this research is there are 19 text types used in the textbooks of the first Grade of State Islamic School. The technique for collecting data is observation which observesthe reason for the use of the text types in the textbooks and then analyzed the reason for the use of the text types in the textbooks by using Miles, Huberman and Saldana model ( 2014: 31) with three steps of data analysis such as abbreviating data, presenting data and picturing and proving conclusion. The findings show that the reason for the use of the text types in the textbooks of the first Grade of State Islamic School is based on the three aspects of context, namely field, tenor and mode. Keywords: Texts, Text Types, Systemic Linguistic,Textbooks